Implementasi Metode CREW dalam Proses Penyiangan Koleksi di Perpustakaan SMA Negeri 6 Pontianak - Anjani, Nabila Desta (Universitas Negeri Padang, 2025)
Collection weeding is an important part of collection management because it involves evaluating and removing or destroying reading materials that no longer meet the criteria needed to maintain the quality of the collection in the library. The purpose of this research discusses the application of the CREW method in the weeding process at SMA Negeri 6 Pontianak Library to improve the quality and relevance of library collections by removing obsolete or irrelevant materials in the library. This research uses a qualitative method with a non-participant observation approach, which allows researchers to observe the phenomenon being studied without being directly involved in the activity. The results showed that before the weeding process, the condition of the collection in the library was still below standard, and the application of the CREW method at SMA Negeri 6 Pontianak Library helped facilitate the weeding process with systematic stages, but there were several obstacles such as limited resources and library policies